Modification of the existing maximum residue level for fluopyram in broccoli - Anastassiadou, Maria (EFSA J, 2019)
In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Bayer Hellas AG submitted a request to the competent national authority in Greece to modify the existing maximum residue level (MRL) for the active substance fluopyram in broccoli. The data submitted in support of the request were found to be sufficient to derive MRL proposals for broccoli. Adequate analytical methods for enforcement are available to control the residues of fluopyram on the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the use of fluopyram according to the reported agricultural practice for broccoli will not result in consumer exposure exceeding the toxicological reference values and therefore are unlikely to present a risk to consumer health.